'I will welcome this one 101%, I will so embrace it': a qualitative exploration of the feasibility and acceptability of HIV self-testing among men who have sex with men (MSM) in Lagos, Nigeria. Issue 6 (3rd September 2020) - Dirisu, Osasuyi; Sekoni, Adekemi; Vu, Lung; Adebajo, Sylvia; Njab, Jean; Shoyemi, Elizabeth; Ogunsola, Sade; Tun, Waimar
Abstract: Men who have sex with men (MSM) are disproportionately affected by HIV in Nigeria. A key strategy in reducing transmission is to increase HIV testing uptake and linkage to treatment for those who test positive. HIV self-testing (HIVST) is an innovative strategy with the potential to increase uptake of HIV testing among key populations at higher risk for HIV. We conducted 23 in-depth-interviews with MSM and two focus group discussions with key opinion leaders to explore perceptions about the feasibility and acceptability of oral HIVST among MSM in Lagos, Nigeria. HIVST was highly acceptable because it was considered convenient to use, painless, private and addressed concerns about stigma. Concerns cited by participants included comprehensibility of instructions to perform and interpret results correctly, as well as lack of support mechanisms to facilitate post-test follow-up and linkage to care. Provision of adequate pre-test information was considered vital as part of the kit distribution process to ensure seamless use of HIVST kits. One-on-one peer-to-peer distribution strategies and retail outlets that facilitate anonymous pick-up are potential distribution channels identified in this study. Overall, our findings suggest that an HIVST program that incorporates these considerations would improve access to HIV testing among MSM in Nigeria.